Development of an e-commerce-based entrepreneurship training model to improve community empowerment: An innovative approach - Dayat Hidayat; Nia Hoerniasih; Iwan Hermawan (Jurnal Cakrawala Pendidikan, 2026)
The purpose of this study is to develop an e-commerce-based entrepreneurship training model to empower the community. The study uses a mixed-method research approach combining quantitative and qualitative Research and Development (R&D). The study population consists of 675 participants in e-commerce-based entrepreneurship training at 23 Community Learning Centers (CLCs) in Karawang Regency, West Java Province, Indonesia, all of whom were included in the study sample. The research steps were carried out as follows: preliminary study, planning, initial product development, expert validation and revision, initial product revision, large-scale product testing, final product development, model effectiveness testing, and implementation and dissemination of the e-commerce-based entrepreneurship training model for community empowerment. The results show that conventional entrepreneurship training has not significantly improved participants' skills and knowledge, leaving the community's entrepreneurial knowledge, attitudes, and skills relatively low. Therefore, an e-commerce-based training model was developed and implemented through planning, implementation, and evaluation stages. The use of the e-commerce-based training model resulted in excellent improvements among participants, particularly in their skills in utilizing e-commerce technology to start and manage online businesses, thereby supporting the research objective of improving the community's skills and knowledge in digital entrepreneurship.